Analisis Praktis Dan Klasifikasi Hadits Dari Segi Kualitasnya: Shahih, Hasan, Dan Dlaif - Fadel Muhammad Muhtadillah; Amar Ma’ruf; Moh. Idris; Diva Kurnia Dwi Salsabilla; Nurul Hidayah Nuha; Shofil Fikri (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Hadith is one of the sources of law in Islamic law, the study of which continues to be conducted and focused on producing legal updates in line with the needs of the times. This research aims to provide a concise understanding of the classification of hadith in hadith science, especially regarding authentic, hasan and dhoif hadith. Hadith is the main source of Islamic teachings after the Al-Qur’an, and its quality is very important to determine the validity and applicability of the teachings contained therein. The research method used is a literature study with a qualitative approach, where various hadith books and the works of ulama are studied to obtain definitions and assessment criteria for each type of hadith. An authentic hadith is a hadith that has a connected sanad (chain of transmitters), a fair and dhabit (strong memory) transmitter, and no illat (flaws) or syaz (irregularities). Hasan hadith has almost the same criteria as authentic hadith, but the degree of fairness or strength of memory of the transmitter is slightly below that of authentic hadith. Meanwhile, dhoif hadith is a hadith that does not meet the criteria for authentic or hasan hadith, either because there are weaknesses in the sanad, the narrator, or there are defects that affect the credibility of the hadith. The research results show that a correct understanding of hadith classification is very important in the study of hadith and its application in everyday life. This knowledge helps Muslims in sorting out the hadith that they can rely on and those that they should be wary of. By understanding the criteria and classification of hadith, Muslims can be more critical and selective in applying teachings originating from hadith, so that they can avoid erroneous or unfounded understandings